Who Gambles in the Stock Market? - KUMAR, ALOK (Journal of Finance, 2009)
ABSTRACT This study shows that the propensity to gamble and investment decisions are correlated. At the aggregate level, individual investors prefer stocks with lottery features, and like lottery demand, the demand for lottery‐type stocks increases during economic downturns. In the cross‐section, socioeconomic factors that induce greater expenditure in lotteries are associated with greater investment in lottery‐type stocks. Further, lottery investment levels are higher in regions with favorable lottery environments. Because lottery‐type stocks underperform, gambling‐related underperformance is greater among low‐income investors who excessively overweight lottery‐type stocks. These results indicate that state lotteries and lottery‐type stocks attract very similar socioeconomic clienteles.